Inconel 713C coating by cold spray for surface enhancement of Inconel 718 - Wu, Kaiqiang (2022)
Inconel 713C is a nickel-based superalloy usually considered as a material of poor weld-ability due to its susceptibility to hot cracking in the heat-affected zones. Cold spray, a solid-state deposition technology that does not involve melting, can be proposed as a methodology to deposit Inconel 713C for surface enhancement of other target components. In this study, Inconel 713C coating was deposited on Inconel 718 substrate with a high-pressure cold spray system. The coating was characterized in terms of microstructure, hardness, and wear properties. The cold-sprayed Inconel 713C coating has a low porosity level and refined grain structures. Microhardness of the Inconel 713C coating was much higher than the Inconel 718 substrate. The sliding wear tests showed that the wear resistance of the cold-sprayed Inconel 713C coating is three times higher than the Inconel 718 substrate, making the coating a suitable protective layer. The main wear mechanisms of the coating include oxidation, tribo-film formation, and adhesive wear.